A Preliminary Study for Identifying Quantitative Trait Loci Associated with Seed Production in Radish Using Genotyping-by-Sequencing - Jinhee Kim; Suhyoung Park; Junho Lee; Koeun Han; Yoonah Jang; Wonbyoung Chae (Horticulturae, 2022)
The high yield of seeds can reduce the cost of seed production for parental lines, as well as F1 cultivars in radish. The number of seeds per silique and silique length are two important traits among traits determining seed yield, but no study has been conducted on their quantitative trait loci (QTLs) in radish. A high-density linkage map was constructed, based on genotyping-by-sequencing (GBS) of the F2 population, derived from two parental lines, significantly differed by the two traits, which were grown in a controlled environment to minimize the environmental effects. Using the map with 848 SNPs, three significant QTLs were identified, two and one of which were associated with the number of seeds per silique and silique length, respectively. Ortholog analysis was conducted with Arabidopsis thaliana genes, related to the number of seeds per silique, and revealed five radish putative candidate genes. These putative candidate genes appear to be related to ovule, embryo sac, embryo, pollen and seed development, as well as a double fertilization process. The method to pollinate the F2 population, as well as preliminary QTLs and SNPs therein, can be helpful for future QTL studies to improve seed production in radish breeding programs.